2009
DOI: 10.2337/dc09-1118
|View full text |Cite
|
Sign up to set email alerts
|

ATLANTIC DIP: Pregnancy Outcome for Women With Pregestational Diabetes Along the Irish Atlantic Seaboard

Abstract: OBJECTIVEProspective evaluation of pregnancy outcomes in pregestational diabetes along the Atlantic seaboard 2006–2007.RESEARCH DESIGN AND METHODSThe Atlantic Diabetes in Pregnancy group, representing five antenatal centers in a wide geographical location, was established in 2005. All women with diabetes for >6 months before the index pregnancy were included. Results were collected electronically via the DIAMOND Diabetes Information System. Pregnancy outcome was compared with background rates.RESULTSThere were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 9 publications
(9 reference statements)
3
53
1
1
Order By: Relevance
“…This is consistent with other studies that continue to show elevated perinatal mortality rates in women with pre-GDM captured past 2003 (13,14,32). Two studies that looked at the trend over time showed a nonsignificant decline in stillbirths/perinatal mortality (13,14).…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with other studies that continue to show elevated perinatal mortality rates in women with pre-GDM captured past 2003 (13,14,32). Two studies that looked at the trend over time showed a nonsignificant decline in stillbirths/perinatal mortality (13,14).…”
Section: Discussionsupporting
confidence: 91%
“…Established in 2006 following approval from the local ethics board, one of its aims is to determine the prevalence of hyperglycaemia in pregnancy and the associated short-and long-term maternal and fetal outcomes [8,9]. Pregnant women whose last menstrual period occurred between September 2006 and March 2009 were eligible to participate in Atlantic DIP.…”
Section: Methodsmentioning
confidence: 99%
“…The Atlantic Diabetes in Pregnancy (Atlantic DIP) partnership was set up in 2005 and serves a population of 500 000 in five regional centers along the Irish Atlantic seaboard, with 11 000 deliveries annually, covering a geographical area of 7338 square miles (8). This partnership advocates universal screening for GDM by a 2 h 75 g oral glucose tolerance test (OGTT) at 24-28 weeks gestation using International Association of Diabetes in Pregnancy Study Group (IADPSG) criteria.…”
Section: Methodsmentioning
confidence: 99%
“…All women diagnosed with GDM in an index pregnancy between January 1st 2006 and December 31st 2007 (nZ323) were invited to participate in this study, which is a substudy of GDM patients from the ongoing Atlantic DIP collaboration (8). We also recalled a control group of women who had normal glucose tolerance (NGT) during an index pregnancy during the same time period in the same location.…”
Section: Methodsmentioning
confidence: 99%